2007
DOI: 10.2320/matertrans.mra2007056
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Electrical Conductivity of Epitaxial BaRuO<SUB>3</SUB> Thin Films Prepared on (001), (110) and (111) SrTiO<SUB>3</SUB> Substrates by Laser Ablation

Abstract: BaRuO 3 (BRO) thin films were prepared on SrTiO 3 (STO) single crystal substrate by laser ablation, and their microstructures and the anisotropy of electrical conductivity were investigated. The (205) and (104) doubly oriented BRO thin film was grown epitaxially on (001) STO substrate. Epitaxial (110) and (009) BRO thin films were obtained on (110) and (111) STO substrates, respectively, at oxygen pressure of 13 Pa and substrate temperature of 973 K. Epitaxial (205) (104) BRO thin film had a tetragonal texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has been reported that hexagonal perovskite thin films of various polymorph phases are grown with a smoother hexagonal terrace structure on the surface of (111) SrTiO 3 (STO) substrates compared to those on (001) or (011) STO substrates, which are found to have orthogonal textures or plate‐like islands, respectively. [ 17,18 ] While some polycrystalline hexagonal perovskite thin films have been studied using X‐ray diffraction and transmission electron microscopy (TEM), [ 19,20 ] the microstructure of the single‐phase thin film has not yet been investigated at the atomic scale, largely owing to the lack of high‐quality epitaxial thin films. The formation mechanism of the high‐quality hexagonal perovskites at the initial stage of growth on (111) cubic‐perovskite substrates would provide crucial information for stabilizing and further strain‐engineering the metastable hexagonal perovskite phases through thin‐film epitaxy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that hexagonal perovskite thin films of various polymorph phases are grown with a smoother hexagonal terrace structure on the surface of (111) SrTiO 3 (STO) substrates compared to those on (001) or (011) STO substrates, which are found to have orthogonal textures or plate‐like islands, respectively. [ 17,18 ] While some polycrystalline hexagonal perovskite thin films have been studied using X‐ray diffraction and transmission electron microscopy (TEM), [ 19,20 ] the microstructure of the single‐phase thin film has not yet been investigated at the atomic scale, largely owing to the lack of high‐quality epitaxial thin films. The formation mechanism of the high‐quality hexagonal perovskites at the initial stage of growth on (111) cubic‐perovskite substrates would provide crucial information for stabilizing and further strain‐engineering the metastable hexagonal perovskite phases through thin‐film epitaxy.…”
Section: Introductionmentioning
confidence: 99%